Living with bipolar disorder a guide for individuals and families - 20160731 frey50; Otto, Michael W. (New York Oxford University Press, 2011)
This book is designed to help patients and their families develop the skills they need to be good consumers of treatment and to become expert partners in the management of this challenging disorder. Drawing on research documenting the strength of combining drug treatments with behavioral interventions for fighting bipolar disorder, the authors of this book take a skill-based, family-and-friends approach to managing the ups and downs commonly experienced with bipolar disorder. Readers will learn how to better recognize mood shifts before they happen, minimize their impact, and move on with their lives.
Part 1: Understanding bipolar disorder and its treatment: -- Introduction -- Description of bipolar disorder -- Medication names and common dosages -- Getting in the habit of taking medications. -- Psychotherapy for bipolar disorder -- Bipolar disorder in adolescents and children. -- Part 2. Managing your disorder: -- Stress and schedule management -- Attention to thinking biases -- Relationships and communication skills -- Managing irritability and anger -- Focusing on life goals -- Mood charting -- Creating a treatment contract -- Improving wellbeing.
Includes index.
Keywords: Manic-depressive illness; Manic-depressive illness -- Treatment; Manic-depressive illness; Bipolar Disorder; Bipolar Disorder -- therapy; Manic-depressive illness; Manic-depressive illness -- Treatment; Popular works